Rancangbangun Mesin Pemarut Gaplek Basah dengan Mekanisme Dua Silinder Pemarut - Winarto Winarto (Jurusan Teknologi Pertanian, 2021)
Tiwul is a staple food substitute for rice which is popular in the community. There are two types of cassava processing into tiwul, namely dry cassava and wet cassava. In general, there are two types of cassava processing into tiwul, namely manual and semi-mechanical, the manual method uses a mortar or pounder, while the semi-mechanical method uses a coconut grater machine. The disadvantage of both methods is that users have to stack and push cassava manually. To overcome this, a grating device is needed that can work without being pushed by the user. The objectives of this research are to design and test the performancy of wet cassava grater using a two-cylinder mechanism. The work procedures used are machine design, machine component manufacturing, component assembly, and machine testing. The wet cassava grater machine with a two-cylinder mechanism has been successfully designed and functioning properly. The rotation of the main shaft cylinder is 1092.67 rpm, slip on the main shaft cylinder is 1.26%, the yield is 82.66%, the engine working capacity is 109.94 kg/hour, and the operating cost is IDR 9.55/kg.